Changes in the shell ornamentation of conchostracans (Phyllopoda, Spinicaudata) at the Permian–Triassic boundary: Case studies from Eastern Europe, Kuznetsk basin, and Verkhoyansk Region - V.V. Zharinova; V.V. Silantiev (Учёные записки Казанского университета: Серия Естественные науки, 2022)
This article sums up the results of our study on shell ornamentation of 13 conchostracan species. Their fossil remains were sampled from the Middle and Upper Permian, Induan, and Olenekian (Lower Triassic) deposits of different zoogeographical provinces. Careful examination of the samples revealed different ornamentation patterns of the outer and middle shell layers: the linear elements of the two layers are set in different directions and together create an intersected structure stiffening the shell. Considering the differences in the number and arrangement of ornamental elements on the growth bands and the shells, three types of ornamentation were singled out: simple (one ornamental element), transitional (two ornamental elements alternating on the shell surface), and complex (more than two ornamental elements arranged in a complex pattern). It was concluded that the combination and arrangement of ornamental elements should be regarded as a valid diagnostic feature of fossil conchostracans at the species and genus ranks. Interestingly, the ornamentation patterns of conchostracans tend to become more complex with time: the shells of Late Permian conchostracans have more twisted ornamentation than Middle Permian ones, but it is less complex than that of Olenekian conchostracans; accordingly, the ornamentation of Early Induan conchostracans is simpler than that of Late Permian and Olenekian ones. This can be explained by the fact that the most opportunistic eurytopic species were more likely to survive in the early phases of the biota recovery after the Great Permian Extinction.